Achieving Lisbon: The EU's R&D challenge. The role of the public sector and implications of US best practice on regional policymaking in Europe - Kim Dobbie Neuer (Hochschule Pforzheim, 2010)
In 2000, the European Council set its sights on becoming the world's top knowledge-based economy. To that end, they aimed to achieve a goal of spending 3% of GDP on research and development by 2010. Their Lisbon Strategy recommended a number of efforts on the European Union and national levels, including encouragement of public-private collaboration. Examination at the regional level indicates the need for R&D and innovation policy to help stimulate growth. Current theory turns attention to the effect of system failure in the regions. The Fraunhofer Institute for Systems and Innovation Research developed a typology for the regions of the European Union. Using performance results, this paper identifies US states that correlate to the typology. Comparative analysis of these states based on key industries and actors, major programs and instruments, successes, failures, impact of federal programs, and best practices then informs discussion of the implications on policymaking. If regional variances represent the most important factor influencing the development of an appropriate policy mix, local specializations, along with regionalized institutional factors, must be considered when codifying the main objectives for policymakers, such as stimulating the efficiency of the system, encouraging dynamic connection among the actors, and reducing the risk of lock-in. This, in turn, affects selection of the instruments that may or may not benefit the region and the indicators with which the impact of public action may be measured. Considering this, particularly challenging for the EU is the need to balance decentralization of action in the regions and coordination at the Union level.
urn:nbn:de:bsz:951-opus-480
Keywords: 330; EU-Wirtschaftspolitik; EU-Forschungspolitik; EU-Staaten; Forschungs- und Technologiepolitik; Connecticut; Maryland; Arizona; Arkansas; USA